PENGARUH KREATIVITAS DAN TRADE EXHIBITION TERHADAP INOVASI BERKELANJUTAN DAN KINERJA PEMASARAN SENTRA INDUSTRI KECIL MEBEL KAYU DI KABUPATEN MADIUN - Sonang Sitohang (Sekolah Tinggi Ilmu Ekonomi Indonesia (STIESIA) Surabaya(STIESIA) Surabaya, 2008)
The research aims are to analyze and test the influence of creativity and trade exhibition toward extended innovation and market performance of small industry of wood furniture cluster in Madiun region. Population are 103 entrepreneurs of wood furniture. Research method uses complete enumeration. Main instrument used in data collection relates to questionnaire through structure 5-points of Likert Scale. Data analysis used is Structural Equation Modeling (SEM) to ensure the causality between previous variable involved validity, reliability test and confirmatory factor analysis. The test requires criterion.The results of research indicate that creativity and trade exhibition significantly influence the extended innovation and innovation significantly influence the market performance, furthermore, both creativity and trade exhibition significantly influence the market performance of small Industry of wood furniture cluster in Madiun.